Melicope moluccana Antimalarial Activity of Furoquinoline Alkaloids from the Leaves of Melicope moluccana - Ryan Ayub Wahjoedi; Ratih Dewi Saputri; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Two furoquinoline alkaloids, leptanoine C (1) and haplopine-3,3´-dimethylallyl ether (2) were isolated from the leaves of Melicope moluccana. The chemical structure of both compounds was determined based on spectroscopic data, including UV, IR, HR-ESI-MS, 1D, and 2D NMR spectral data. The antimalarial activity of compounds 1-2 against Plasmodium falciparum 3D7 showing their IC50 values are 0.18 ppm and 2.28 µg/mL, respectively.